2021
DOI: 10.1111/spsr.12480
|View full text |Cite
|
Sign up to set email alerts
|

Variations of Public Opinion Towards Face Veiling: Arguments in the Swiss Debate

Abstract: This study focuses on public opinion towards the face veiling of Muslim women and investigates the possibility of identifying different groups of citizens supporting distinct combinations of arguments regarding face veiling criticisms. Two groups are expected to argue for or against face veiling. Also, two other groups are expected to vary depending on their idea of liberalism inherent in face‐veiling arguments: a specific way of life versus respect for different ways of life. Using latent class (regression) a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…The astonishing yet interesting findings were political group which opposed the idea of veiling, religious acceptance of veiling appeared complex however, they agreed that this way of life is best for women, their identity and protection and no threat to others [16]. A Study evaluated social anxiety through a scale among the female students with prior hypothesis but the results did not establish any sort of significance and rejected the hypothesis [17]. These results do not go with the present study as it was conducted among western world and no scale for anxiety was incorporated as well.…”
Section: Discussionmentioning
confidence: 93%
“…The astonishing yet interesting findings were political group which opposed the idea of veiling, religious acceptance of veiling appeared complex however, they agreed that this way of life is best for women, their identity and protection and no threat to others [16]. A Study evaluated social anxiety through a scale among the female students with prior hypothesis but the results did not establish any sort of significance and rejected the hypothesis [17]. These results do not go with the present study as it was conducted among western world and no scale for anxiety was incorporated as well.…”
Section: Discussionmentioning
confidence: 93%
“…Similarly, a study in Switzerland found that 15% of the Swiss strongly agree with any argument against the Muslim practice of wearing a face veil and have negative anti-Muslim and anti-Islam attitudes (Eugster, 2021). Findings of these studies indicate that a minority of the public displays indiscriminately negative attitudes towards Muslims, and that the rejection of practices cannot be completely reduced to prejudicial feelings towards Muslims.…”
Section: Prejudice-based Rejection Of Muslim Practicesmentioning
confidence: 96%
“…Further, a recent study in the Netherlands showed that between 17% and 30% of the population feel positive towards Turks and Moroccans and accept their rights, yet sometimes object to the wearing of the headscarf or the founding of Islamic schools . Similarly, a study from Switzerland (Eugster, 2021) found that around 35% of the Swiss population was positive towards Muslims, yet objected to full face veil which was perceived as oppressive and going against self-determination of women.…”
Section: Principle-based Rejection Of Muslim Practicesmentioning
confidence: 99%
See 1 more Smart Citation